Growth of the Pacific jack Caranx caninus (Pisces: Carangidae) from the coast of Colima, México - Elaine Espino Barr; Manuel Gallardo Cabello; Esther Guadalupe Cabral Solís; Arturo Garcia Boa; Marcos Puente Gómez (Revista de Biología Tropical, 2008)
The Pacific jack Caranx caninus is a common species fished by artisanal fishermen off the coast of Colima, México. During 2002, monthly samples of morphometric data and otoliths were taken to determine age and growth. Seven age groups were identified. The highest growth, 14.4 cm, takes place during the first year of life. During the second year, C. caninus grows 11.76 cm; the third year 9.61 cm; the fourth 7.85 cm; the fifth 6.41 cm and sixth year 5.24 cm. The constants of von Bertalanffy´s growth equation were: L∞ = 83.26 cm, W∞ = 18.138 g, K = 0.202, t o = -0.283 and A0.95 = 15 years. Growth curves of other species of the same genus were calculated in order to compare them with the one obtained in the present work. The gonadosomatic index presented higher values during November and May. The periods of more intensive feeding are from August to February. Rev. Biol. Trop. 56 (1): 171-179. Epub 2008 March 31. El jurel Caranx caninus es una especie común que se captura en la pesca artesanal frente a las costas de Colima, México. Mensualmente, durante 2002, se tomaron datos morfométricos y muestras de otolitos para determinar la edad y el crecimiento. Se encontraron siete grupos de edad; durante el primer año de vida se da el mayor crecimiento, hasta 14.4 cm. Durante el segundo año, C. caninus crece 11.76 cm; el tercero 9.61 cm; el cuarto 7.85 cm; el quinto 6.41 cm y el último año crece 5.24 cm. Las constantes de la ecuación de crecimiento de von Bertalanffy fueron: L∞ = 83.26 cm, W∞ = 18.138 g, K = 0.202, to = -0.283 y la longevidad A0.95 = 15 años. Las curvas de crecimiento de otras especies del mismo género se compararon con las obtenidas en el presente trabajo. El índice gonadosomático presentó valores más altos durante noviembre y mayo. Los periodos de tiempo de alimentación más intensa son de agosto a febrero.